The Austro-marxist and the Bolshevik attitude toward the national question - Mandić, Stefan (Sociološki pregled, 2023)
The main goal of this paper is to examine the attitude of Austro-Marxists and the Bolsheviks toward the national question, these being two important currents of Marxism in the early 20th century, Marx and Engels believed that the main historical actor was the economic class and that with the development of means of production, and the emergence of communism, nations would eventually wither away. Маny of the most prominent Marxists of the second generation were more inclined to this position. On the other hand, Austro-Marxists and the Bolsheviks were the first Marxist currents to develop a somewhat comprehensive theory of the nation, due to practical-political needs. The former ones were interested in preserving the Austro-Hungarian Empire as a multiethnic state, while the latter aimed to exploit national tensions as one of the instruments for revolutionary seizure of power in Russia.